The Role of Islamic Education Policies in Improving Teacher Quality at Madrasah Aliyah - Tengku Darmansah; Mia Sri Dwi Yanti; Zahara Salma; Hadi Purnomo (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study is grounded in the role of Islamic education policies in improving teacher quality through the integration of a tahfizh Al-Qur’an program as a comprehensive curriculum, aimed at strengthening Islamic character education based on memorization in alignment with the Ministry of Religious Affairs curriculum and the Joint Decree of Three Ministers (SKB 3 Menteri). The purpose of this research is to analyze institutional policies such as memorization scheduling, the methods of tasmi, takrir, and murojaah, discipline monitoring, teacher development through daily supervision, and periodic evaluation. The research employed a qualitative approach, with data collected through in-depth interviews with the vice principal for curriculum affairs. The findings show that indicators of success include the cultivation of a daily murojaah culture, regular memorization examinations, the awarding of tahfizh certificates, motivational support from parents, a conducive Sharia-based environment, and collaborative efforts within the madrasa ecosystem. These elements collectively strengthen students’ memorization quality and enhance teachers’ competence holistically. This educational policy has successfully shaped an integrated Islamic education model that harmonizes formal academics with spiritual development and is therefore recommended for replication in other madrasas to optimize educator quality.